Effects of temperature and light during the veraison period on grape berry growth - Qian Zha; Haixia Zhong; Meiling Tang; Xiangjing Yin; Pengpeng Sun; Aili Jiang; Xiaojun Xi; Jiuyun Wu (Plant Stress)
Temperature and light are key environmental factors in plant fruit development that affect fruit coloring, sugar accumulation, and softening. Here, grape berries were grown in vitro to investigate the effects of different temperatures and light treatments on their quality, with a focus on analyzing the effects of anthocyanin metabolism pathway genes and related metabolites. Both high temperature and low light affected grape coloring; however, differences were observed among varieties. Anthocyanins respond to high temperature and low light conditions through a balancing of metabolite types. The COP1–HY5 signaling pathway, which regulates the expression of FLS4, was affected by light and temperature. High temperatures were beneficial for sugar accumulation but resulted in fruit softening, and weak light affected sugar accumulation but did not cause fruit softening. This study was conducted to elucidate poor grape quality under high temperatures and weak lighting following a large-scale application of these conditions to facility-grown grapes. Our results provide valuable insights with respect to grape production. Effective cultivation measures should be considered to improve existing production problems and lay a solid theoretical foundation for growing high-quality grapes.